1994
DOI: 10.1002/cne.903480405
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic study on the development of the carotid body and glomus cell groups distributed in the wall of the common carotid artery and its branches in the chicken

Abstract: Development of the carotid body and the glomus cell groups in the wall of the common carotid artery and its branches was studied in chickens at various developmental stages by electron microscopy. At 8 days of incubation, the carotid body anlage consisted of mesenchyme-like cells, whereas the clusters of epithelial cells, which occasionally contained a few dense-cored vesicles and were accompanied by unmyelinated nerve fibers, were located in the region surrounding the carotid body anlage and in the wall of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 20 publications
4
20
0
Order By: Relevance
“…During embryonic development, all glomus cells exhibit intense immunoreactivity for NPY and tyrosine hydroxylase besides serotonin and chromogranin A, regardless of their residential places. Electron microscopic study (Kameda, 1994) has confirmed that at 8 days of incubation the carotid body rudiment consists of mesenchyme-like cells, whereas the clusters of epithelial cells, which occasionally contain a few dense-cored vesicles and are accompanied by unmyelinated nerve fibers, are located in the region surrounding the carotid body rudiment and in the wall of the common carotid artery. The glomus cells of the carotid body and around the arteries in the chicken seem to be émigrés that arrive in each residential place from the distal vagal ganglion.…”
Section: Development Of Glomus Cellsmentioning
confidence: 60%
See 1 more Smart Citation
“…During embryonic development, all glomus cells exhibit intense immunoreactivity for NPY and tyrosine hydroxylase besides serotonin and chromogranin A, regardless of their residential places. Electron microscopic study (Kameda, 1994) has confirmed that at 8 days of incubation the carotid body rudiment consists of mesenchyme-like cells, whereas the clusters of epithelial cells, which occasionally contain a few dense-cored vesicles and are accompanied by unmyelinated nerve fibers, are located in the region surrounding the carotid body rudiment and in the wall of the common carotid artery. The glomus cells of the carotid body and around the arteries in the chicken seem to be émigrés that arrive in each residential place from the distal vagal ganglion.…”
Section: Development Of Glomus Cellsmentioning
confidence: 60%
“…The cells are also widely distributed in the wall of the common carotid artery and its branches. The presence of TuJ1 immunoreactivity in the cytoplasm of glomus cells has been shown by immunoelectron microscopy (Kameda et al, 1994). Thus, glomus cells seem to differentiate along the neural lineage.…”
Section: Development Of Glomus Cellsmentioning
confidence: 95%
“…The importance of having a correct level of oxygenation for the normal development of the carotid body during the postnatal period could also apply during the embryonic phases. In the chicken, the early buds of the carotid bodies reach their final location at the bifurcation of the brachycephalic arterial trunk by embryonic day 8 (29), and the characteristics of mature glomus cells are recognized a few days later (15). Hence, if the blunting in hypoxic hyperventilation were due mainly to the effects of hypoxia on the functional development of the carotid body, it would mean that this occurred during the last half of the embryonic period.…”
Section: Discussionmentioning
confidence: 99%
“…Kusakabe et al (1987) later confirmed the role of the g-s connection in controlling vascular tone of the carotid labyrinth as described in the Introduction. Thereafter, the g-s connection has been observed in the glomus cells in the wall of the common carotid artery and its branches of the domestic fowl (Kameda, 1990a(Kameda, , 1994. In Cynops pyrrhogaster, the cytoplasmic processes are closely associated with the endothelial cells (Fig.…”
Section: Light and Electron Microscopymentioning
confidence: 94%